Rezolvaţi ecuaţiile
a)
b)
c)
Răspunsuri la întrebare
Răspuns de
3
Răspuns de
2
a)
2 x - 7 = 4 x + 3
4 x + 3 = 2 x - 7
4 x - 2 x = - 7 - 3
2 x = - 10
x = ( - 10 ) : 2
x = - 5
b)
4 x - 5 x + 5 = - 2 x + 4
- x + 2 x = 4 - 5
x = - 1
c)
3 x / 4 - ( 1 - 2 x ) / 3 = 6 x / 6 - 7 / 6
cmmmc al numitorilor ( 4; 3; 6 ) = 12
9 x - 4 ( 1 - 2 x ) - 12 x = - 14
9 x - 4 + 8 x - 12 x = - 14
17 x - 12 x = - 14 + 4
5 x = - 10
x = ( - 10 ) : 5
x = - 2
Alte întrebări interesante
Matematică,
8 ani în urmă
Matematică,
8 ani în urmă
Matematică,
8 ani în urmă
Matematică,
9 ani în urmă
Matematică,
9 ani în urmă
Matematică,
9 ani în urmă